2011
DOI: 10.1002/jbm.b.31816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical polarization and composition of biphasic calcium phosphates on early stage osteoblast interactions

Abstract: In spite of having excellent biocompatibility and osteogenic property of hydroxyapatite (HAp) and β-tricalcium phosphate (β-TCP), concerns have been raised regarding their degradation kinetics. Complete in vivo degradation of HAp takes years because of its slow degradation rate, and fast degradation rate of β-TCP limits its application. Biphasic calcium phosphates (BCPs) composed of both HAp and β-TCP have controlled degradation to some extent. Here, we have prepared three different BCPs composed of β-TCP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…In comparison to non-poled ones, Tarafder et al, however, observed fewer cell-cell attachments with the extension of filopodia on positively poled surfaces. These morphological differences went along with a delayed initial proliferation [41], irrespective of the sign of the surface charge. Research on osteoblast-like cells in some cases supports the preference of negatively charged surfaces [42], albeit in other cases contradicts this trend [43].…”
Section: Christophis Et Al Biointerphases 2013 8:27mentioning
confidence: 94%
“…In comparison to non-poled ones, Tarafder et al, however, observed fewer cell-cell attachments with the extension of filopodia on positively poled surfaces. These morphological differences went along with a delayed initial proliferation [41], irrespective of the sign of the surface charge. Research on osteoblast-like cells in some cases supports the preference of negatively charged surfaces [42], albeit in other cases contradicts this trend [43].…”
Section: Christophis Et Al Biointerphases 2013 8:27mentioning
confidence: 94%
“…Contact angle depends on many factors, for instance, surface roughness, surface chemistry, and grain size. 27 Because nHA is more hydrophilic as an inorganic material than PEEK, and the nHA/ PEEK composite is rougher than PEEK, the improvement in hydrophilicity seen with the nHA/PEEK composite may stem from changes in the surface roughness and chemistry, 27,28 which may have affected the functions of the osteoblasts in this study.…”
mentioning
confidence: 88%
“…We observe that levels of ALP expression relative to the smooth non-conductive silk foams were increased on the rougher conductive scaffolds both without and with electrical stimulation ( Figure 2D). We believe that this is a result of differences in the surface chemistry altering protein deposition from the medium onto the scaffolds, [30] which Bose and coworkers show to modify cell-material interactions in vitro, [32] yet Epinette and Manley conclude that microstructure and surface charge are not the sole factors at play in osteoinduction in the clinic. [33] Indeed, our experimental data for non-conductive silk foams and conductive silk foams without/with electrical stimulation enabled us to observe that electrical stimulation markedly enhanced calcium deposition and collagen production (Figures 2E and F and 3).…”
Section: In Vitro Cell Culturementioning
confidence: 99%